A simple optoelectronic tongue discriminates amino acids - Wang, Benhua; Han, Jinsong; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
A self-assembled nine-element optoelectronic tongue consisting of a positively charged water-soluble poly(para-phenyleneethynylene) and three metal ions (Fe2+, Co2+, and Cu2+) at three different pH values (7, 10, and 13) discriminates all of the 20 natural amino acids in water. Unknown identification was not ideal. Addition of a highly positively charged green fluorescent protein in the presence of Fe2+, Co2+, and Cu2+ increased the unknown identification to above 86 %. Linear discriminant analysis (LDA) orders the responses according to the amino acid type, that is, hydrophobic, polar, anionic, or cationic.